2016
DOI: 10.1116/1.4948341
|View full text |Cite
|
Sign up to set email alerts
|

XPS depth profiling of an ultrathin bioorganic film with an argon gas cluster ion beam

Abstract: The growing interest in artificial bioorganic interfaces as a platform for applications in emerging areas as personalized medicine, clinical diagnostics, biosensing, biofilms, prevention of biofouling, and other fields of bioengineering is the origin of a need for in detail multitechnique characterizations of such layers and interfaces. The in-depth analysis of biointerfaces is of special interest as the properties of functional bioorganic coatings can be dramatically affected by in-depth variations of composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To ensure that the silane molecules only adsorbed on the surface, modified PEDOT:PSS films were sputtered using an argon cluster ion beam, and the XPS spectra of the layers sputtered for different times were recorded. In contrast to monoatomic ion beams, the gas cluster ion beam does not destroy chemical bonds in organic materials, allowing the collection of depth profiles of the chemical composition of the studied samples. In Figure C, the atomic concentrations of fluorine and sulfur were plotted as a function of the sputter time; the eight cycles of sputtering led to the formation of a crater approximately 20 nm deep. The rapid decrease in fluorine signal already observed in the first sputtering cycle indicates that the 3FS molecules adsorbed selectively on the surface and did not penetrate the PEDOT:PSS film.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that the silane molecules only adsorbed on the surface, modified PEDOT:PSS films were sputtered using an argon cluster ion beam, and the XPS spectra of the layers sputtered for different times were recorded. In contrast to monoatomic ion beams, the gas cluster ion beam does not destroy chemical bonds in organic materials, allowing the collection of depth profiles of the chemical composition of the studied samples. In Figure C, the atomic concentrations of fluorine and sulfur were plotted as a function of the sputter time; the eight cycles of sputtering led to the formation of a crater approximately 20 nm deep. The rapid decrease in fluorine signal already observed in the first sputtering cycle indicates that the 3FS molecules adsorbed selectively on the surface and did not penetrate the PEDOT:PSS film.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the ultrathin oligoglucose bioorganic films deposited on the oxidized silicon wafers were sputtered by Ar n + GCIB at 10 keV and 10 nA and analyzed using an XPS technique. 86 It was found that there was no substantial damage during Ar 2500 + gas cluster sputtering to the ultrathin carbohydrate layers, which was underpinned by a stable chemical composition versus sputter-time. Self-assembled monolayers (SAMs) have been widely studied as promising hybrid systems for practical applications in electronics and so on.…”
Section: Gas Cluster Ion Beam Etchingmentioning
confidence: 99%